Fake-Vertising and Mobile Games: Case Study of ‘Pull the Pin’ Ads - Mago, Zdenko (Communication Today, 2020)
The mobile games segment currently represents the biggest share of the global game market with the highest year-on-year growth rate. Logically, the importance of mobile game marketing is increasing as well. However, some practices operate ‘on the edge’. Utilising ads presenting fake gameplay footage, which can mislead potential new gamers and lure them to install such games, has become quite common and tolerated advertising practice (so far). This study examines the design and forms of already implemented fake ads on mobile games, concentrating particularly on the case study of originally fictional ‘pull the pin’ mechanics devised for this purpose and utilised by several games’ promotions. The study aims to investigate how misrepresentations concerning ‘pull the pin’ fake ads on mobile games influence their overall rating expressed through the gamers’ reviews of selected games on Google Play, as well as the impact of fake ads on other aspects of the mobile gaming sector by applying a discursive analysis.